Simple power analysis attack on random pseudo operations - Min WANG; Zhen WU (Tongxin xuebao)
Random pseudo-operations on elliptic curve scalar multiplication algorithm,less secure than it claimed by simple power analysis (SPA)attacks.Even in the single curve SPA,it leaks lots of useful key information.Multiple curve recursive approximation attack(MCRAA),a new multiple curve SPA attack,was proposed to get all of the key information with a small curve set.When the length of the key is n,the size of the set is O(lbn) which was confirmed by experiment.